Social support and dental caries experience: Findings from the Hispanic Community Health Study/Study of Latinos Sociocultural Ancillary Study. Issue 5 (27th February 2021) - Laniado, Nadia; Sanders, Anne E.; Fazzari, Melissa J.; Badner, Victor M.; Singer, Richard H.; Finlayson, Tracy L.; Hua, Simin; Isasi, Carmen R.
Abstract: Objective: To examine the association of social support with dental caries experience in Hispanics/Latinos living in the United States (US) and to assess whether the relationship is modified by nativity status. Methods: This cross‐sectional study analysed data for 4459 dentate men and women aged 18‐74 years in the Hispanic Community Health Study/Study of Latinos (HCHS/SOL) Sociocultural Ancillary Study. At baseline (2008‐2011), dentists quantified dental caries experience as the number of decayed, missing, and filled permanent tooth surfaces (DMFS) for all teeth excluding third molars. Social support was assessed according to measures of structural support (Social Network Index) and functional support (Interpersonal Support Evaluation List). Covariate‐adjusted multiple linear regression estimated the relationship between social support and dental caries experience and tested whether the association was modified by nativity status (born within the 50 US states, foreign‐born <10 years in the United States, foreign‐born >10 years or more in the United States). Results: In covariate‐adjusted models, each additional role in the social network was associated with 1.39 fewer DMF tooth surfaces (95% CI: −2.21, −0.58) among foreign‐born Hispanics/Latinos with fewer than 10 years lived in the US. For foreign‐born Hispanics/Latinos with 10 years or more in the United States, each additional social network role was associated with 0.57 fewer DMF tooth surfaces (95% CI: −1.19, 0.04). No association was observed between functional social support and dental caries experience regardless of nativity status. Conclusions: Our findings suggest that structural social support is protective against dental caries experience among recent immigrants of Hispanic/Latino background. This association may reflect the importance of social support to integration into the medical and dental infrastructure and thus receipt of dental care. Future research that examines the behavioural and cultural factors that moderate the relationship between social support and dental caries experience will inform development of culturally sensitive dental caries prevention programs for Hispanics/Latinos in the United States.